Effectiveness of Physical Activity Intervention on ADHD Symptoms: A Systematic Review and Meta-Analysis - Xie, Yongtao; Gao, Xuping; Song, Yiling; Zhu, Xiaotong; Chen, Mengge; Yang, Li; Ren, Yuanchun (Frontiers in Psychiatry, 2021)
Abstract Objective: To assess the effectiveness of physical activity (PA) intervention on attention-deficit/hyperactivity disorder (ADHD) related symptoms. Method: Studies implemented PA intervention for ADHD symptoms were identified through searching for PubMed, Web of Science, Cochrane Library, and Embase databases from inception through June 2021. Standardized mean difference (SMD) with 95% confidence interval (CI) was used to assess the effectiveness of PA intervention on improving ADHD symptoms. The meta-analyses were conducted using fixed-effects or random-effects models according to the heterogeneity between studies. Results: Nine before-after studies (232 participants) and fourteen two-group control studies (162 participants/141 controls) were included in this meta-analysis. Combined results for before-after studies indicated significant improvements in all studied ADHD symptoms (inattention: SMD = 0.604, 95%CI: 0.374–0.834, P < 0.001; hyperactivity/impulsivity: SMD = 0.676, 95%CI: 0.401–0.950, P < 0.001; emotional problems: SMD = 0.416, 95%CI: 0.283–0.549, P < 0.001; behavioral problems: SMD = 0.347, 95%CI: 0.202–0.492, P < 0.001). Meta-analyses for two-group control studies further confirmed that PA intervention significantly improved the inattentive symptom (SMD = 0.715, 95%CI: 0.105, 1.325, P = 0.022). Subgroup analyses suggested that PA might especially beneficial for inattention and hyperactivity/impulsivity reduction in children compared to adults (P for interaction were 0.027 and 0.005, respectively). Moreover, closed motor skills were beneficial for hyperactive/impulsive problems (SMD = 0.671, P < 0.001), and open motor skills were beneficial for attention problems (SMD = 0.455, P = 0.049). Given to the limited sample size, the best frequency and intensity of PA intervention need further investigation. Conclusion: Our results suggest that PA intervention can improve attention problems in ADHD, and may be more beneficial for ADHD children. Closed-skill and open-skill sports are beneficial for hyperactivity / impulsivity and attention problems, separately. Further high-quality randomized clinical trials with large sample are needed.